Integration of Local Wisdom in the Implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Policy in The Biology Education Study Programs in Indonesia: Analysis and Evaluation - Sugiharto, Bowo (Biotik, 2024)
This study analyzes the implementation of the “Merdeka Belajar Kampus Merdeka (MBKM)” program in the Biology Education Study Program (BESP) on various campuses in Indonesia with a special focus on the integration of local wisdom. Data was collected from respondents in 44 study programs covering aspects such as campus status, accreditation, course repositioning, implementation of MBKM activities, and suggestions and recommendations for program improvement. The results of the analysis show that the majority of study programs at state campuses (75%) have repositioned the curriculum and implemented various forms of MBKM activities such as student exchanges (70.45%), internships/work practices (68.18%), and teaching assistance. The integration of local wisdom is emerging as an important aspect, with many study programs using local wisdom in academic activities and business product development, such as using traditional medicinal plants for health products. Key suggestions from respondents included the need for standardization of guidelines, financial assistance for students, periodic evaluations, and adjusting the curriculum to the needs of the times. Most study programs have ensured that MBKM activities follow the formulated Program Learning Outcomes (PLO), with 63.64% of study programs stating that they always ensure this suitability. However, there are still challenges in the process of recognizing MBKM activities into courses and integrating these activities into a thesis or final project, with 77.27% of study programs not carrying out this integration. The study concludes that although MBKM has been doing well, there is still room for improvement. There needs to be further efforts in terms of integrating local wisdom, financial support, and strengthening collaboration between educational institutions and local communities. Clear and standardized implementation of guidelines, as well as continuous evaluation, are essential to improve the effectiveness and benefits of the MBKM program.